PDCD10 promotes the tumor-supporting functions of TGF-β in pancreatic cancer - Zhou, Qianwen; Breitkopf-Heinlein, Katja; Gaitantzi, Haristi; Birgin, Emrullah; Reißfelder, Christoph; Rahbari, Nuh Nabi (Clinical science, 2024)
The progression of pancreatic ductal adenocarcinoma (PDAC) is significantly affected by transforming growth factor (TGF)-β but targeting TGF-β can also compromize physiological effects in patients.Our study examined the functions of the ubiquitously expressed protein, PDCD10, as a modulator of TGF-β signaling in PDAC. Using in silico analyses we found that in patient samples, PDCD10 is significantly higher expressed in PDAC tumor tissue compared with normal pancreas and it is highly correlated with reduced survival. We created stable KO’s of PDCD10 in two PDAC lines, PaTu 8902 (SMAD4 +/+) and PaTu 8988t (SMAD4 -/-), and found that KO lines are more sensitive to 5-FU and Gemcitabine treatment than their wild-type counterparts. Performing viability and wound closure assays we further found that PDCD10 promotes cell survival and proliferation by enhancing specifically the mitogenic functions of TGF-β. The molecular mechanism underlying this effect was further investigated using Western blots and with primary organoid lines derived from patient PDAC tissue samples. The data imply that PDCD10 mediates an increase in p-ERK through a non-SMAD4 pathway, leading to EMT promotion. Furthermore, PDCD10 facilitates deactivation of RB via a SMAD4-dependent pathway, thereby counter-acting the anti-proliferative actions of TGF-β. By performing proximity ligation assays (PLA) we found that PDCD10 associates with the kinase MST4, translocates it intracellularly and thereby facilitates phosphorylations of RB and ERK1/2.Our study indicates that PDCD10 promotes the proliferative function and EMT induction of TGF-β in pancreatic cancer cells. Therefore, targeting PDCD10 in PDAC patients could represent a promising new strategy to optimize TGF-β targeted therapies.